Предмет: Химия,
автор: intrepid
Осуществите превращения: Fe2O3=>(+C,t)=>(Cl2)=>(NaOH)=>(t)=>(+Al)=>(+S)=>(+O2)=>(+H2SO4)
Ответы
Автор ответа:
0
Fe2O3=>(+C,t)=>(Cl2)=>(NaOH)=>(t)=>(+Al)=>(+S)=>(+O2)=>(+H2SO4) = 2Fe2O3=>т.к. образуется 2 атома (+C,t)=>2 (Cl2)=> 4(NaOH)=>(t)=>(+Al)=>(+S)=>(+O2)=> в результате реакции возникает 2(+H2SO4)
Автор ответа:
0
Fe2O3 + 3C --(t°)--> 2Fe + 3CO↑
2Fe + 3Cl2 = 2FeCl3
FeCl3 + 3NaOH = Fe(OH)3↓ + 3NaCl
2Fe(OH)3 --(t°)--> Fe2O3 + 3H2O
Fe2O3 + 2Al --(t°)--> Al2O3 + 2Fe
Fe + S --(t°)--> FeS
4FeS + 7O2 = 2Fe2O3 + 4SO2
Fe2O3 + 3H2SO4 = Fe2(SO4)3 + 3H2O
2Fe + 3Cl2 = 2FeCl3
FeCl3 + 3NaOH = Fe(OH)3↓ + 3NaCl
2Fe(OH)3 --(t°)--> Fe2O3 + 3H2O
Fe2O3 + 2Al --(t°)--> Al2O3 + 2Fe
Fe + S --(t°)--> FeS
4FeS + 7O2 = 2Fe2O3 + 4SO2
Fe2O3 + 3H2SO4 = Fe2(SO4)3 + 3H2O
Похожие вопросы
Предмет: Кыргыз тили,
автор: bekzanmukanbetov383
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: aisok